EVALUATION OF ANTIBACTERIAL POTENTIAL OF EPHEDRA FOLIATA BOISS. EX. C. A. MEY - SHARAD BISSA (The Bioscan, 2015)
The present study is an attempt to evaluate the antimicrobial potential of different plant part extracts (aqueous, alcoholic, chloroform and petroleum ether) of a gymnospermous plant Ephedra foliata Boiss. ex C.A.Mey. against human pathogenic (E.coli, Salmonella typhi, Klebsiella pneumoniae and Enterobacter aerogenes) as well as plant pathogenic (Agrobacterium tumefaciens) bacteria using disc diffusion method. All the plant parts exhibited antibacterial activity. The maximum antibacterial activity in Ephedra foliata, was presented by petroleum ether extract of dried stem against Klebsiella pneumoniae and dried leaves against Enterobacter aerogenes. Phytochemical analysis (Stem part) was also done. Thin Layer Chromatography (TLC) identity test was also performed which corresponded to the ephedrine present in the plant.